Netazepide, an Antagonist of Cholecystokinin Type 2 Receptor, Prevents Vincristine-Induced Sensory Neuropathy in Mice - Amandine Bernard; Mohamad Mroué; Sylvie Bourthoumieu; Malcolm Boyce; Laurence Richard; Franck Sturtz; Claire Demiot; Aurore Danigo (Pharmaceuticals, 2024)
Among the vinca-alkaloid class, vincristine is a potent chemotherapeutic agent with significant neurotoxic effects and is employed to address a wide spectrum of cancer types. Recently, the therapeutic potential of the cholecystokinin type 2 receptor (CCK2R) as a target for vincristine-induced peripheral neuropathy (VIPN) was demonstrated. In this study, the impact of preventive CCK2R blockade using netazepide (Trio Medicines Ltd., London, UK) was investigated in a mouse model of vincristine-induced peripheral neuropathy. Netazepide is a highly selective CCK2R antagonist under development for the treatment of patients with gastric neuroendocrine tumors caused by hypergastrinemia secondary to chronic autoimmune atrophic gastritis. Vincristine-induced peripheral neuropathy was induced by intraperitoneal injections of vincristine at 100 µg/kg/d for 7 days (D0 to D7). Netazepide (2 mg/kg/d or 5 mg/kg/d, per os) was administered one day before vincristine treatment until D7. Vincristine induced a high tactile allodynia from D1 to D7. VIPN was characterized by dorsal root ganglion neuron (DRG) and intraepidermal nerve fiber (IENF) loss, and enlargement and loss of myelinated axons in the sciatic nerve. Netazepide completely prevented the painful symptoms and nerve injuries induced by vincristine. In conclusion, the fact that netazepide protected against vincristine-induced peripheral neuropathy in a mouse model strongly supports the assessment of its therapeutic potential in patients receiving such chemotherapy.